2001
DOI: 10.4141/a00-118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent cold exposure varying in intensity on core body temperature and resting heat production of beef cattle

Abstract: . 2001. Effects of intermittent cold exposure varying in intensity on core body temperature and resting heat production of beef cattle. Can. J. Anim. Sci. 81: 459-465. Crossbred beef heifers (n = 18) fed at 1.3× maintenance were exposed to summer daytime temperatures (20 ± 0.2°C) for 8 h (08:00 until 16:00) and to control (22°C), moderate (-6°C) or cold (-15°C) environments for 16 h daily (16:00 until 08:00) for a minimum 21-d adaptation period to investigate the effects of intensity of intermittent cold expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…In fact, the ∆T vag for all treatments in the present study were 50 to 60% higher than the control value (2.47°C) of our previous study (Bergen et al 2001). High control room temperature in the present study (27.1°C) compared with that (21.8°C) of Bergen et al (2001), coupled with cool outdoor nighttime temperatures (Fig.…”
Section: Resultsmentioning
confidence: 43%
See 4 more Smart Citations
“…In fact, the ∆T vag for all treatments in the present study were 50 to 60% higher than the control value (2.47°C) of our previous study (Bergen et al 2001). High control room temperature in the present study (27.1°C) compared with that (21.8°C) of Bergen et al (2001), coupled with cool outdoor nighttime temperatures (Fig.…”
Section: Resultsmentioning
confidence: 43%
“…When overall means were compared, there was no effect of interval or treatment on MeanT vag , MaxT vag or MinT vag (P ≥ 0.49; Table 1) as was also the case in our previous study (Bergen et al 2001) where beef heifers were exposed to 21.8, -6.3 or -15.2°C for 16 h d -1 for 21 d. However, whereas no effect of cold-exposure on HoursOver and ∆T vag (P ≥ 0.29; Table 1) was found in the present study, we (Bergen et al 2001) found previously that these parameters were both elevated with each of the two cold-exposure treatments. In fact, the ∆T vag for all treatments in the present study were 50 to 60% higher than the control value (2.47°C) of our previous study (Bergen et al 2001).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations